Citizens of the world : U.S. women and global government - Threlkeld, Megan (Power, politics, and the world., 2022)
"Citizens of the World excavates the work of a variety of women-white, Black, radical, moderate, liberal, socialist-who asserted both their right and their responsibility to shape and fully participate in efforts to govern the world. Between 1900 and 1950, many politically active women in the United States advocated for greater geopolitical integration in order to end war. They argued that increasing global interdependence demanded both governmental cooperation and a broader commitment to the international community rather than to nationalist entrenchment, and they believed that ordinary women and men around the world had a responsibility to further that commitment. Over these five decades, some women called for agreements to arbitrate and adjudicate conflicts, others for formal intergovernmental institutions, and still others for a full-fledged world federation. They believed a politically organized world, whatever form it took, was necessary for lasting peace. Despite various differences among them-and there were many-all of these women saw themselves as part of a global effort to end war that required them to act as equal members of an international body politic. In other words, they saw themselves as world citizens"--